1995
DOI: 10.1002/mpo.2950250304
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated total‐body irradiation preceding high‐dose cytosine arabinoside as a preparative regimen for bone marrow transplantation in children with acute leukemia

Abstract: Twenty children with acute leukemia between 3 and 19 years of age underwent allogeneic bone marrow transplantation from HLA-matched sibling donors after conditioning with total-body irradiation (1,200 cGy in six fractions of 200 cGy twice daily for 3 days) and high dose cytosine arabinoside (3 g/m2 given every 12 hours for 12 doses). Three patients died with acute toxicity. Six patients developed grade II acute graft versus host disease. With a median follow-up of 68 months (range 26-96 months), thirteen child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(4 reference statements)
3
6
0
Order By: Relevance
“…1,3 In the setting of HSCT, the reported incidence of keratoconjunctivitis due to high-dose cytarabine in combination with TBI is 45-75%, although most reports have not mentioned the incidence of kerato-conjunctivitis, much less prophylactic measures against kerato-conjunctivitis. [4][5][6][7] In accordance with these reports, the results of our study indicated that the patients who received high-dose cytarabine and TBI frequently develop moderate to severe kerato-conjunctivitis (66%). Of note is that during highdose cytarabine therapy, all our patients received topical corticosteroid every 6 h, which has been reported to effectively prevent cytarabine-induced kerato-conjunctivitis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1,3 In the setting of HSCT, the reported incidence of keratoconjunctivitis due to high-dose cytarabine in combination with TBI is 45-75%, although most reports have not mentioned the incidence of kerato-conjunctivitis, much less prophylactic measures against kerato-conjunctivitis. [4][5][6][7] In accordance with these reports, the results of our study indicated that the patients who received high-dose cytarabine and TBI frequently develop moderate to severe kerato-conjunctivitis (66%). Of note is that during highdose cytarabine therapy, all our patients received topical corticosteroid every 6 h, which has been reported to effectively prevent cytarabine-induced kerato-conjunctivitis.…”
Section: Discussionsupporting
confidence: 89%
“…1,3 In the setting of hematopoietic stem cell transplantation (HSCT), particularly in allogeneic HSCT, high-dose cytarabine is generally used in combination with TBI and/or other chemotherapeutic agents such as CY. [4][5][6][7][8][9] In contrast to a non-HSCT setting, this kerato-conjunctivitis has not been described as a clinically significant toxicity or has been disregarded as a minor toxicity in HSCT recipients. We have evaluated and reported the efficacy and safety of a conditioning regimen consisting of TBI and high-dose cytarabine for allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…5 Ara-C/TBI regimens have also been evaluated, and reported outcomes were similar to those obtained with the CY/TBI regimen. [22][23][24] In some reports comparing HDAC/TBI regimens with CY/TBI regimens, no advantage in using the HDAC/TBI regimens was demonstrated, 25,26 while other reports showed that the HDAC/TBI regimens were more toxic. 27 Some investigators reported that HDAC-containing regimens were highly effective in reducing relapse rate after BMT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that mouth rinse during and shortly after high-dose cytarabine infusion is an effective and inexpensive measure to reduce the incidence of moderate to severe (particularly severe) oral mucositis in patients receiving high-dose cytarabinecontaining intensive regimen for allogeneic HSCT. Although the incidence of oral mucositis varies among the conditioning regimens, the regimen consisting of high-dose cytarabine and TBI has been known to cause oral mucositis at a high incidence (65-100%) [2][3][4][5][6]. Mouth rinse or mouth wash is generally recommended as a care in patients with oral mucositis to reduce the risk of mucositis-associated infection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cytarabine is one of the chemotherapeutic agents used in conditioning regimens for HSCT. In combination with TBI, high-dose cytarabine causes oral mucositis in about 65-100% of patients [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%